(untitled) (PROKLA. Journal of Critical Social Science, 2020)
International ecological inequality is a precondition for the growth-led ‘development’ currently unfolding at the global level with disastrous environmental and social impacts. As ecologically unequal exchange, international trade leads to the constriction of the ecological operating space of some while expanding that operating space for others. This not only allows for further growth but also exacerbates already existing ecological inequalities and asymmetrical power relations.